Hvad er ærefrygt? - Sørensen, Christian Egelund (Religionsvidenskabeligt Tidsskrift, 2023)
ENGLISH ABSTRACT: In this article, I present an analysis of research into the ex-perience of awe. Awe has been characterized as an emotion encompassing a perceived vastness, a need for cognitive accommodation, so that the individual might assimilate the new and overwhelming experience and, ultimately, attain a feeling of meaning-fulness. Additionally, I present Edmund Burke’s concept of the sublime and Rudolf Otto’s notion of the numinous in order to illuminate the most important characteris-tics of awe-like experiences. I proceed to present the hypothesis that experiences of awe originate in experiences of prediction errors. Prediction errors occur with a mis-match between anticipated sensory data and the actual data. I argue that experiences of such errors on a massive scale can explain feelings of vastness, the need for cogni-tive accommodation, and meaningfulness, and more fundamentally, why certain per-ceptions illicit experiences of awe, while others do not. DANSK RESUMÉ: I denne artikel præsenterer jeg en analyse af forskning af ære-frygt (engelsk: awe). Ærefrygt er blevet karakteriseret som en emotion kendetegnet ved følelsen af oplevet storhed, et behov for en kognitiv tilpasning til den nye og overvældende situation og en følelse af meningsfuldhed. Jeg præsenterer yderligere Edmund Burkes begreb om det sublime og Rudolf Ottos tanke om det numinøse for at kunne belyse de afgørende træk i ærefrygt. På baggrund af dette foreslår jeg, at ære-frygt kan forklares ud fra en hypotese om, at ærefrygt har sit ophav i oplevelsen af massive ‘prediction errors’. Det kan forklare følelserne af storhed, behovet for kognitiv tilpasning og meningsfuldhed, som andre forskere tilsyneladende har identificeret. Yderligere kan en sådan hypotese mere grundlæggende forklare, hvorfor visse sanse-indtryk virker ærefrygtindgydende. Jeg præsenterer derefter en række spørgsmål, som bør indgå i fremtidige undersøgelser.